2004
DOI: 10.1093/ps/83.3.462
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Laying Hens Seal Blubber Oil: Effects on Egg Yolk Incorporation, Stereospecific Distribution of Omega-3 Fatty Acids, and Sensory Aspects

Abstract: Seventy-two 26-wk-old Single Comb White Leghorn laying hens were randomly assigned to 36 cages (2 per cage) in a 3-orthogonal 4 x 4 latin square, with the fourth row suppressed, to assess the effect of feeding refined seal blubber oil (SBO, containing 22.2% omega-3 fatty acids) on the fatty acid composition and position in the egg yolk lipids. The experiment was conducted over a period of 9 wk. Eggs were collected and numbered, and the weights were recorded for each week and cage. Eggs collected at wk 5 and 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 44 publications
8
50
0
8
Order By: Relevance
“…However, Hargis (1988) suggested that egg yolk cholesterol showed little or no variation in response to genetic, pharmacological or dietary manipulation. Moreover, Schreiner et al (2004) did not find any differences in the yolk cholesterol content in response to dietary n-3 PUFA.…”
Section: --mentioning
confidence: 69%
See 1 more Smart Citation
“…However, Hargis (1988) suggested that egg yolk cholesterol showed little or no variation in response to genetic, pharmacological or dietary manipulation. Moreover, Schreiner et al (2004) did not find any differences in the yolk cholesterol content in response to dietary n-3 PUFA.…”
Section: --mentioning
confidence: 69%
“…According to Schreiner et al (2004), egg production was not significantly affected because of including fish oil in commercial layer diets. However, Cortinas et al (2003) summarised that egg production was significantly higher when laying hens were fed diets containing 4% fish oil or flaxseed oil.…”
mentioning
confidence: 98%
“…It is also important to point out that for general consumers of omega-3 products, small differences in colour, if detected, would be of secondary importance because colour is a minor important parameter in functional foods. The association between low sensory quality of eggs and dietary fi sh oils has long been recognized (Holdas and May, 1966): a negative effect on yolk aroma, taste and fl avour when laying hens were fed with a fi sh oil diet were reported recently by different authors (Gonzalez-Esquerra and Leeson, 2000;Schreiner et al, 2004;Carrillo-Domínguez et al, 2005). In some cases, a small percentage of panelists reported an unpleasant aroma and/or taste in the experimental diets, but this was also the case in the control diet, so these data are not conclusive.…”
Section: Discussionmentioning
confidence: 98%
“…Common dietary sources of omega-3 fatty acids include fi sh, crustaceans and mollusks, but there are other sources, such as linseed or marine microalgae. The use of these sources in laying hen diets in order to obtain enriched eggs may have negative effects, not only on hen health (Aymond et al, 1994;Van Elswysk et al, 1994;Bean and Lesson, 2003), but also on egg quality parameters and laying hen yields (Collins et al, 1997;Baucells et al, 2000;Gonzalez-Esquerra and Leeson, 2000;Schreiner et al, 2004).…”
Section: N-3 Polyunsaturated Fatty Acid-enriched Eggsmentioning
confidence: 99%
“…Some of the fatty-acid sources added to layer diets are linseed oil (used for the production of ω-3 enriched oil), soybean oil and sunflower, which are used as sources of mono-and polyunsaturated fatty acids (Baucells et al, 2000;Schreiner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%